Regular dessins d'enfants with field of moduli Q(root p of 2) - Hidalgo, Rubén A. (Ars mathematica contemporanea, 2017)
Herradon has recently provided an example of a regular dessin d'enfant whose field of moduli is the non-abelian extension ?$\mathbb{Q} (\sqrt3{2})$? answering in this way a question due to Conder, Jones, Streit and Wolfart. In this paper we observe that Herradon's example belongs naturally to an infinite series of such kind of examples; for each prime integer ?$p ≥ 3$? we construct a regular dessin d'enfant whose field of moduli is the non-abelian extension ?$\mathbb{Q} (\sqrtp{2})$?; for? $p=3$? it coincides with Herradon's example.
Keywords: definicijsko polje; modulsko polje; Riemannove ploskve